Response of wheat (Triticum aestivum) to poultry manure rates in Maiduguri, Nigeria - AHMAD ABUBAKAR SADDIQ; AISHA ABDULLAHI MAHMUD; IBRAHIM ALI LASSA; ABDULLAHI BUKAR; MOHAMMED TIJJANI GUBIO; MAHMOUD DOGARA ABDULRAHMAN (Asian Journal of Agriculture, 2025)
Abstract. Saddiq AA, Mahmud AA, Lassa IA, Bukar A, Gubio MT, Abdulrahman MD. 2025. Response of wheat (Triticum aestivum) to poultry manure rates in Maiduguri, Nigeria. Asian J Agric 9: 800-807. Wheat (Triticum aestivum) production in semi-arid Nigeria is limited by poor soil fertility and high fertilizer costs. This study assessed the effects of poultry manure on wheat performance during two dry seasons (2022/2023 and 2023/2024) at the University of Maiduguri Teaching and Research Farm in Maiduguri, Nigeria. A randomized complete block design with three replications tested five manure rates (0, 2.5, 5, 7.5, and 10 t/ha). Growth traits (plant height, tiller number, and days to heading) and yield components (spikelets per spike, 1000-grain weight, and grain yield) were measured. Poultry manure significantly improved soil fertility and crop performance compared to the control. Grain yield rose more than six-fold, peaking at 10 t/ha (≈3.5 t/ha). However, 7.5 t/ha achieved nearly equivalent yields (≈3.2 t/ha) while delivering a more favorable cost–benefit ratio. Moderate manure rates also improved spikelet number and grain filling without nutrient imbalance observed at the highest rate. These results highlight poultry manure as a sustainable, low-cost alternative to chemical fertilizers, with 7.5 t/ha identified as the most practical rate for boosting wheat yield and profitability in semi-arid smallholder systems. In addition to yield enhancement, the study provides insight into how organic inputs can restore declining soil quality in marginal environments where resource-poor farmers struggle to afford conventional fertilizers. The observed improvements in vegetative growth and reproductive development indicate that poultry manure supplies a balanced nutrient release that supports wheat throughout its growth cycle. The two-season evaluation also demonstrates the consistency of poultry manure effects under varying dry-season conditions, confirming its reliability as an organic amendment. Overall, the findings contribute to ongoing efforts to promote climate-smart and resource-efficient agronomic practices in northern Nigeria. The recommendation of 7.5 t/ha aligns with the need for affordable strategies that enhance food security while maintaining soil health for long-term wheat production.